Industrial Training Report: Perpustakaan Laman Hikmah Universiti Teknikal Malaysia Melaka (UTeM) / Muhammad Abd Rahim - Abd Rahim, Muhammad (Faculty of Information Management, 2018)
Industrial training is one of the requirements from the Faculty of Information Management and the trainee need to provide a report regarding the internship period in order to complete their studies. The trainee will includes what have been learnt about library management. The reports are dividing into five sections. Internship brief, introduction about the Universiti Teknikal Malaysia Melaka (UTeM), the information about the organization, the training activities includes daily activities, special projects and extra activities. The last section contains the industrial training reflections which are application of knowledge, skills and experience in undertaking the task, personal taught and opinion, lesson learnt and limitation and recommendations. All these sections have been explained with the details information and the picture and workflows includes for certain part. The report also included with the references and appendices.